Spatial distribution of southern brown shrimp (Farfantepenaeus subtilis) on the Amazon continental shelf: a fishery, marine geology and GIS integrated approach - MARTINS, Déborah Elena Galvão (Universidade Federal do Pará, 2017)
The spatial distribution of the southern brown shrimp Farfantepenaeus subtilis (Pérez-Farfante, 1967) was studied based on industrial fishing fleet activities and is associated with geological and oceanographic characteristics of the benthonic environments on the Amazon continental shelf. Using a geographical information system (GIS) this paper sought to calculate the relative abundance of brown shrimp based on catch per unit effort (CPUE) and compare it with bathymetry, type of sedimentary structure, sedimentation rate and bottom salinity. As a result, we have concluded that the relative abundance (in terms of CPUE) is not uniformly distributed in space. Spatial analysis indicates that commercial trawling efforts were made in the (foreset) region of the subaqueous Amazon delta at depths of 40 to 60 m. In this region, prawn are responsible for the bioturbation of the sediments and the creation of a sedimentary structure called mottled mud. In the foreset region, sedimentation rates progressively increased up to 10 cm.yr-1; re-suspension was reduced and bottom salinity was high (~ 36). It appears that all of these factors define a stable muddy area with intense bioturbation. This notable biological activity is to be explained by the occurrence of a high F. subtilis abundance that appears to originate in a microbial loop. We concluded that by combining fishery information with environmental data from a GIS, it was possible to identify abundance distribution patterns for southern brown shrimp and other economically important fishery resources and to understand how they change on a large spatial-scale.